2018
DOI: 10.21276/ambi.2018.05.1.ra01
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal Effect of Stem bark Exudate Against Commiphora swynnertonii Rhipicephalus appendiculatus

Abstract: Introduction:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Then, egg production index, oviposition, product efficacy (De Sousa et al, 2020;Temba et al, 2018) and lethal dose (LC 50 and LC 99 ) were calculated using prior calculated female's initial weight, egg mass weight and hatching percentage. Egg production index (EPI) was calculated using the equation: Oviposition reduction (OR) was obtained according to the equation:…”
Section: Sensitivity Of a Oryzae On Adult Ticksmentioning
confidence: 99%
“…Then, egg production index, oviposition, product efficacy (De Sousa et al, 2020;Temba et al, 2018) and lethal dose (LC 50 and LC 99 ) were calculated using prior calculated female's initial weight, egg mass weight and hatching percentage. Egg production index (EPI) was calculated using the equation: Oviposition reduction (OR) was obtained according to the equation:…”
Section: Sensitivity Of a Oryzae On Adult Ticksmentioning
confidence: 99%
“…The laid eggs were kept under the same conditions to hatch, and failure to hatch indicated that the egg was not viable and this was observed visually. Then, egg production index, oviposition, product efficacy (De Sousa et al, 2020;Temba et al, 2018) and lethal dose (LC50 and LC99) were calculated using prior calculated female's initial weight, egg mass weight and hatching percentage.…”
Section: Adult Sensitivity Testmentioning
confidence: 99%
“…Product efficiency (PE) was estimated by the formula: %𝑃𝐸 = ((𝑅𝐸 𝑐𝑜𝑛𝑡𝑟𝑜𝑙 𝑔𝑟𝑜𝑢𝑝 − 𝑅𝐸 𝑒𝑥𝑝𝑒𝑟𝑖𝑚𝑒𝑛𝑡𝑎𝑙 𝑔𝑟𝑜𝑢𝑝) ÷ (𝑅𝐸 𝑐𝑜𝑛𝑡𝑟𝑜𝑙 𝑔𝑟𝑜𝑢𝑝)) × 100 De Sousa et al, 2020;Temba et al, 2018).…”
Section: Adult Sensitivity Testmentioning
confidence: 99%